The Impact of the Introduction of Innovative REDS Scale for the Evaluation of Central Tunnelled Catheter (CTC) Exit Site on Infection Prevention in Long-Term Haemodialyzed Patients - Porazko, Tomasz; Stasiak, Edyta; Klinger, Marian (Frontiers in Surgery, 2021)
Central tunnelled catheter (CTC)-related infections are a leading cause of a catheter loss, thus being the source of significant morbidity and mortality. The study aims at evaluating the impact of the implementation of the innovative REDS scale (devised by the authors) for the description of the tunnel condition on the frequency of infective complication in long-term catheter users. A group of 40 end-stage kidney disease (ESKD) patients dialysed through CTC were evaluated. For two years, each dialysis session was preceded by the assessment using the REDS scale. The results, as well as follow-up evaluation of participants, were compared with a two-year period of treatment before the tool was introduced. The two-year cumulative incidence of CTC exit site infection (ESI) has dropped significantly (log-rank p < 0.001): from 0.89 episode per 1000 catheter days (53.5%, CI95 [35.9%; 66.2%]) in the period before REDS was used – to 0.26 episode per 1000 catheter days (18.6%, CI95 [6.1%; 29.4%]) in the time of REDS application. There were also significantly fewer episodes of ESI complicated with catheter-related blood stream infection (CRBSI) requiring the CTC removal (0.6 episode per 1000 catheter days; 18.6%, CI95 [6.1%; 29.4%] vs. 0.3 episode per 1000 catheter days; 4.7%, CI95 [0.0;10.7%]; log-rank p = 0.04, in pre-REDS and REDS, time respectively). The REDS scale appears to be a simple, cost-effective tool reducing the frequency of the tunnelled CTC exit site infection and associated bloodstream infections.